Inhibition phenomena between Salmonella strains--a new aspect of salmonella infection control in poultry - Martin, G.; Barrow, P. A.; Berchieri, A. [UNESP]; Methner, U.; Meyer, H. (My University, 1996)
Freshly hatched chickens show a very high susceptibility to Salmonella infections and control measures are therefore frequently focused on the period shortly after hatching. Experimental investigations using one strain against itself, differentiated by different antibiotic resistance markers, have shown that colonisation with Salmonella prevents the establishment of subsequently inoculated challenge organisms in the chicken gut. The inhibition effect lasts for several days and is detectable even when a challenge dose of 108 organisms is used. It is independent of the breed of bird. Chickens colonised with Salmonella shed a subsequently inoculated challenge strain with significant lower numbers for several weeks than do non colonised control birds. The phenomenon is strain specific but not serovarspecific as has been shown in investigations using different strains of the same and other serovars for colonisation and challenge. The phenomenon shows a large variability between strains. Using other Enterobacteriaceae strains comparable inhibition against Salmonella was not observed. One important topic for further investigation is the capability of Salmonella live vaccines given orally to establish a protection effect, based on the inhibition phenomenon in the first few days of live, developing into a long-lasting immunity when the birds reach immunological maturity.
Inhibition between Salmonella-strains - A new aspect of Salmonellosis control in poultry